Insights on Molecular Characteristics of Hydrochars by 13C-NMR and Off-Line TMAH-GC/MS and Assessment of Their Potential Use as Plant Growth Promoters - Fregolente, Laís G [UNESP]; Dos Santos, João Vitor [UNESP]; Vinci, Giovanni; Piccolo, Alessandro; Moreira, Altair B. [UNESP]; Ferreira, Odair P.; Bisinoti, Márcia C [UNESP]; Spaccini, Riccardo (MDPI, 2021)
Hydrochar is a carbon-based material that can be used as soil amendment. Since the physical-chemical properties of hydrochar are mainly assigned to process parameters, we aimed at evaluating the organic fraction of different hydrochars through 13C-NMR and off-line TMAH-GC/MS. Four hydrochars produced with sugarcane bagasse, vinasse and sulfuric or phosphoric acids were analyzed to elucidate the main molecular features. Germination and initial growth of maize seedlings were assessed using hydrochar water-soluble fraction to evaluate their potential use as growth promoters. The hydrochars prepared with phosphoric acid showed larger amounts of bioavailable lignin-derived structures. Although no differences were shown about the percentage of maize seeds germination, the hydrochar produced with phosphoric acid promoted a better seedling growth. For this sample, the greatest relative percentage of benzene derivatives and phenolic compounds were associated to hormone-like effects, responsible for stimulating shoot and root elongation. The reactions parameters proved to be determinant for the organic composition of hydrochar, exerting a strict influence on molecular features and plant growth response.
Keywords: hydrothermal carbonization; molecular characteristics; plant growth promoter; sugarcane residues; water-soluble fractions